History is complicated. Narrate and communicate the Shoah in the classroom - Antonella Tiburzi (Didattica della storia, 2020)
Teaching the history of the Shoah requires a high level of attention and a deep awareness of the complexity of the subject. The need to create a curriculum arises from the need to deepen a methodology capable of educating the "History of the Shoah" through concrete indications of procedure valid for the formation of the various contents. Therefore, it is necessary to create a broad path that includes targeted tools, accurate methodologies and adequate resources aimed at effective education. Over the years of experience and study, especially in the training studies and practices in Israel and during the various comparisons and meetings with the teachers of history of the Anglo-Saxon world, it emerged that this practice had proved particularly useful especially for Italian teachers, who had never received specific training and method and who therefore needed to develop precise and targeted skills aimed at exercising this accurate teaching.